The Effect Of Position Promotion And Mutation On The Performance Of Administrator Officials In Tomohon City Government - Karundeng, Ventje Florensianus; Lumingkewas, Lexi; Mamonto, Fitri (Technium Social Sciences Journal, 2023)
Promotion and Mutation are activities that increase work productivity, as well as guarantee employee development. By carrying out promotion and mutation, it is interpreted as giving appreciation based on the final work of employees in the agency. With appreciation, employees are expected to have high performance. This study aims to 1) To analyze and provide an overview of whether there is an effect of Promotion on the Performance of Official Administrators in Tomohon City Government; 2) To find out and give an overview of whether there is an effect of mutations in the Tomohon City Government and to analyze the relationship between mutations on the performance of Administrator Officers in the Tomohon City Government; 3) To analyze and provide an overview of whether there is an effect of simultaneous promotion and mutation on the performance of administrator officials in the Tomohon City Government. The research method used is a quantitative research method with a total population of 133 administrators in the Tomohon City Government. The sample that was set was 30 people and the research instrument used was a questionnaire. The data analysis technique uses the IBM SPSS Version 26 program. Based on the research results, hypothesis testing shows that 1) Promotion partially has a significant effect on the Performance of Administrator Officers in the Government of Tomohon City; 2) Mutation partially does not have a significant effect on the Performance of Administrative Officers in Tomohon City Government; 3) Promotion and Mutation simultaneously have a significant influence on the Performance of Administrative Officers in the Government of the City of Tomohon.